1985
DOI: 10.1037/0022-006x.53.6.890
|View full text |Cite
|
Sign up to set email alerts
|

Structure of problem behavior in adolescence and young adulthood.

Abstract: Earlier bivariate findings suggested that diverse problem behaviors, including problem drinking, illicit drug use, delinquent-type behavior, and precocious sexual intercourse, may comprise a single behavioral syndrome in samples of normal adolescents. A multivariate test of this possible syndrome was carried out through a series of maximum likelihood factor analyses based on self-report data from several samples of adolescents and youth. Analyses were performed by sex on four waves of panel data from a high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

67
641
5
27

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,005 publications
(746 citation statements)
references
References 27 publications
67
641
5
27
Order By: Relevance
“…First order factors were selected from factor analytic studies examining the personality and behavioral characteristics underlying the co-occurrence of antisocial and substance use disorders in adolescence and adulthood (Donovan & Jessor, 1985;Krueger et al, 2002;McGee & Newcomb, 1992). The criminal behavior factor score was derived from a preliminary confirmatory factor analyses of eight criminal behavior items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First order factors were selected from factor analytic studies examining the personality and behavioral characteristics underlying the co-occurrence of antisocial and substance use disorders in adolescence and adulthood (Donovan & Jessor, 1985;Krueger et al, 2002;McGee & Newcomb, 1992). The criminal behavior factor score was derived from a preliminary confirmatory factor analyses of eight criminal behavior items.…”
Section: Methodsmentioning
confidence: 99%
“…This study extends prior historical research by using a factor-analytic model of the theoretically and empirically-grounded construct of deviance proneness as a predictor of adolescent marijuana use. Our latent construct of deviance proneness was informed by not only earlier notions of problem behavior theory (Donovan & Jessor, 1985;McGee & Newcomb, 1992), but more contemporary understanding of the "externalizing spectrum" (Krueger et al, 2002). Further, unlike prior historical studies, this study's model of deviance proneness combined measures of conduct problems (i.e.…”
Section: Current Study Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Research findings are consistent with a number of explanations --causal, correlational, cultural, and coincidental (see Leigh, 1990a for discussion). These various explanations emphasize very different factors, from pharmacological disinhibition (see Crowe & George, 1989;Room & Collins, 1983), to cognitive decrements (Pernanen, 1976;Steele & Southwick, 1985), risk-taking or sensation-seeking personality tendencies (Adlaf & Smart, 1983;Zuckerman, 1979), "problem behavior syndrome" (Donovan & Jessor, 1985;Osgood, Johnston, O'Malley & Bachman, 1988), to expectations about the effects of alcohol (see Wilson, 1978), the use of intoxication as an excuse for unacceptable behavior (Critchlow, 1983;Lang, 1985;MacAndrew & Edgerton, 1969), or the role of situation-specific rituals Wilson, 1981).…”
Section: Issues Of Interpretation and Preventionmentioning
confidence: 99%
“…Although the empirical relationship is well documented, the nature of the association is less well understood. The purpose of the current article is to identify the factor structure of measures of risky sexual behavior and substance use in women and to examine personality characteristics associated with these behaviors.Early studies, including male and female adolescents and adults, have revealed that the variance among measures of risky behaviors can be adequately explained by a single first-order factor, labeled "unconventionality" (e.g., Donovan & Jessor, 1985 (Fromme, Katz, & Rivet, 1997). …”
mentioning
confidence: 99%